Вы находитесь на странице: 1из 17

EXACT DIFFERENTIAL

EQUATIONS
The expression

M ( x, y ) dx + N ( x, y ) dy ……(1)
is called exact (or Total) differential if there exist a
function f ( x , y ) of two real variables such that the
expression equals the differential df. We know that
∂f ∂f
df = dx + dy ……………….(2)
∂x ∂y ∂f
Thus if equation (1) is exact then M ( x, y) = = fx
∂x
∂f
N ( x, y) = = f y …….(3) If (1) is an exact differential
∂y
then DE
M ( x , y ) dx + N ( x , y ) dy = 0
is called an exact differential equation.
As from eqs (1), (2) & (3) we have
∂M ∂ f2
∂N ∂ f 2
= ...and... =
∂y ∂y∂x ∂x ∂x∂y

where the functions M(x,y) and N(x,y) have continuous


first order Partial derivatives, therefore
∂ f2
∂ f 2
=
∂y∂x ∂x∂y
Hence criteria for Eq to be an Exact equation is
∂M ∂N
=
∂y ∂x
Solution of an Exact Equation
For finding of the solution of an exact
equation we integrate M(x,y) w r t x
regarding y as a constant. Then integrate w
r t y only those terms of N(x,y) which are
free from x. The sum of these two
expressions thus obtained are equated to a
constant. The solution is

∫ Mdx +
y = constant
∫ Ndy = c
Free from x
Solution of an Exact Equation (2nd Method)

If M ( x , y ) dx + N ( x , y ) dy = 0 ……(1)
is exact then there exist a function f(x,y) such that
∂f ∂f
df = dx + dy = Mdx + Ndy ..( 2)
∂x ∂y
Therefore ∂f ∂f
== N ... and ... = M.....(3)
∂y ∂x
Integrating eq (2) w r t x
f ( x, y) = ∫ Mdx +h( y )..( 4)

Where h(y) is treated as constant of integration.


Diff eq (4) w r t y, we get ∂f ∂f dh
∂y
=
∂y
[ ∫ Mdx ] +
dy
Using eq (3) we have
∂ dh
N =
∂y
[ ∫ Mdx ] +
dy
dh ∂

dy
=N −
∂y
[ ∫ Mdx ]...( 5)
Integrating eq (5) w r t y, we obtain h(y) and hence from
eq (4) f ( x , y ) =c is the required solution of DE (1).
Solve(tan x + 2 y )dy + ( y sec 2
x + sec x tan x )dx = 0
Soln: Here
N = tan x + 2 y .. & .. M = y sec x + sec x tan x
2

∂M ∂N
⇒ = sec x ..and ...
2
= sec x
2

∂y ∂x
⇒ eq is exact
The solution is
∫ Mdx +
y = constant
∫ Ndy = c
Free from x

∫ ∫
⇒ ( y sec x + sec x tan x )dx + 2 ydy = c
2
⇒ y tan x + sec x + y = c
2
Solve(tan x + 2 y )dy + ( y sec 2
x + sec x tan x )dx = 0
Soln: Here
N = tan x + 2 y .. & .. M = y sec x + sec x tan x
2

∂M ∂N
⇒ = sec x ..and ...
2
= sec x
2

∂y ∂x
⇒ eq is exact
The solution is f ( x , y ) = c1 But
f ( x, y) = ∫ Mdx +h( y )


⇒ ( y sec 2 x + sec x tan x )dx +h(y)
⇒ f ( x , y ) = y tan x + sec x + h(y) ......(2)
Diff eq (4) w r t y, we get
∂f dh ⇒tan x + dh = N
=tan x +
∂y dy dy
dh dh
⇒tan x + =tan x +2 y⇒ =2 y
dy dy
⇒h( y ) = y 2 +c 2
Put the value of h(y) in eq (2)

⇒ f ( x , y ) = y tan x + sec x + y + c 2 ....(3)


2
As f ( x , y ) = c1

So eq (3) will become

y tan x + sec x + y + c 2 = c1
2

⇒ y tan x + sec x + y = c
2
Solve ( 3 x + 4 xy )dx + ( 2 x + 2 y )dy = 0
2 2

Soln: Here M = 3 x + 4 xy ... and ... N = 2 x + 2 y


2 2

∂M ∂N
⇒ = 4 x .. and ... =4x
∂y ∂x
⇒ eq is exact
The solution is ∫
Mdx +
y = constant
∫ Ndy = c
Free from x

∫ ∫
⇒ ( 3 x 2 + 4 xy )dy + 2 ydy = c

⇒x + 2 x y + y = c
3 2 2
Solve ( xe xy
+ 2 y )dy + ye dx = 0 ..when ..y(0) = 1
xy

Soln: Here M = ye ... and ... N = xe


xy xy
+2y
∂M ∂N
⇒ = e + xye ..and ...
xy xy
= e + xye
xy xy

∂y ∂x
⇒ eq is exact
∫ Mdx + ∫ Ndy = c
The solution is y = constant Free from x

⇒ ∫ ye ∫
dx + 2 ydy = c
xy
⇒e xy
+ y =c
2

When x=0 then y=1

⇒ 1+1=2

⇒e xy
+ y =2
2
Solve( x 2
+ 4 y )dy + ( 2 xy − 3)dx = 0 ..when ..y(1) = 2

Soln: Here M = 2 xy − 3... and ... N = x + 4 y


2

∂M ∂N
⇒ = 2 x ..and ... = 2x
∂y ∂x
⇒ eq is exact
∫ Mdx + ∫ Ndy = c
The solution is y = constant Free from x

∫ ∫
⇒ ( 2 xy − 3)dx + 4 ydy = c
⇒x y − 3 x + 2 y = c
2 2

When x=1 then y=2

⇒ 2-3+8=c ⇒c = 7

⇒x y − 3 x + 2 y = 7
2 2
Solve

( y sec x + sec x tan x )dx + (tan x + 2 y )dy = 0


2

solve 3− y y − 2x
2
[ 2 ]dx + [ 2
]dy = 0..when..y(-1) = 2
x xy